Characterization of enzymes involved in the interconversions of different forms of vitamin B6 in tobacco leaves - Huang, ShuoHao; Zeng, HaiBin; Zhang, JianYun; Wei, Shu; Huang, LongQuan (Plant physiology and biochemistry, 2011)
There are six different vitamin B₆ (VB₆) forms, pyridoxal (PL), pyridoxamine (PM), pyridoxine (PN), pyridoxal 5′-phosphate (PLP), pyridoxamine 5′-phosphate (PMP) and pyridoxine 5′-phosphate (PNP). PLP is a coenzyme required by more than 100 cellular enzymes. In spite of the importance of this vitamin, the understanding of VB₆ metabolic conversion in plants is limited. In this study, we developed a sensitive and reliable method to assay VB₆-metabolizing enzyme activities by monitoring their products visually using high-performance liquid chromatography. With this method, the reactions catalyzed by PL/PM/PN kinase, PMP/PNP oxidase, PM-pyruvate aminotransferase, PL reductase and PLP phosphatase were all nicely detected using crude protein extracts of tobacco leaves. Under optimal in vitro conditions, specific activities of those enzymes were 0.15 ± 0.03, 0.10 ± 0.03, 0.08 ± 0.02, 0.64 ± 0.13 and 23.08 ± 1.98 nmol product/min/mg protein, respectively. This is the first report on the conversion between PM and PL catalyzed by PM-pyruvate aminotransferase in plants. Furthermore, the PL reductase activity was found to be heat inducible. Our study sheds light on the VB₆ metabolism taking place in plants.